2018
DOI: 10.1111/apv.12183
|View full text |Cite
|
Sign up to set email alerts
|

Grey networks: The contradictory dimensions of Australia's immigration detention system

Abstract: The notion of dark networks has recently received attention in the literature on policy network analysis. Dark networks are defined as illegal and covert, in contrast to bright networks which are legal and overt. In this article, we suggest a third category – grey networks – which are characterised by their use of secrecy and concealment despite their ostensibly legal status. These networks are subject to contradictory imperatives. They employ methods that cannot be openly acknowledged within the larger legal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Overall, the policy of mandatory detention has been frequently criticised by human rights activists and health researchers (Neil & Peterie, 2018). Nonetheless, this study revealed some benefits in short-term and definite detention for new arrivals, including creating a sense of safety and security, and providing an opportunity for asylum seekers to recover from previous physical and psychological traumas before facing the challenges of living in a new sociocultural environment.…”
Section: Discussionmentioning
confidence: 77%
“…Overall, the policy of mandatory detention has been frequently criticised by human rights activists and health researchers (Neil & Peterie, 2018). Nonetheless, this study revealed some benefits in short-term and definite detention for new arrivals, including creating a sense of safety and security, and providing an opportunity for asylum seekers to recover from previous physical and psychological traumas before facing the challenges of living in a new sociocultural environment.…”
Section: Discussionmentioning
confidence: 77%
“…Research on governance networks (Ramia et al, 2018) is helpful in developing a conceptual platform for the administration of harm. This work highlights the complex and often clandestine networks of stakeholders whose actions and decisions shape outcomes (Neil and Peterie, 2018). Working with and alongside governments, various stakeholders – including powerful corporations and public organisations – play an important part in designing harm.…”
Section: Overview Of Conceptsmentioning
confidence: 99%
“…Extensive research undertaken by one of the authors between 2015 and 2020 underlines the ubiquity of violence within these facilities, not only in terms of overt physical and sexual attacks that disproportionately harm women and children, but also through the infliction of micro-level indignities, deprivations and frustrations (Neil and Peterie, 2018; Peterie, 2018a, 2018b, 2021, 2022). Psychologically speaking, these constant abrasions impose a ‘death by a thousand cuts’, harming detainees, while also extending to negatively impact their loved ones. Detainee's Partner: It's a terrible path to go to be involved with someone like this, because you see detention from the inside – the violence of it.…”
Section: Examples Of the Administration Of Harmmentioning
confidence: 99%
“…Participants in this study testified to the Kafkaesque nature of immigration detention. Detention, as they experienced it, was a scheme of constantly shifting permissions and prohibitions -a world in which unpredictable rules dictated the small details of asylum seekers' lives (Peterie 2018a;2018b;Neil & Peterie 2018). These visitors also underlined the human costs associated with the scheme, offering vivid examples of the anguish that detention produced in the asylum seekers they visited.…”
Section: Negotiating Privilegementioning
confidence: 99%